Mid-level providers in emergency obstetric and newborn health care: factors affecting their performance and retention within the Malawian health system - McAuliffe Eilish; Bradley Susan (BMC, 2009)
Abstract Background Malawi has a chronic shortage of human resources for health. This has a significant impact on maternal health, with mortality rates amongst the highest in the world. Mid-level cadres of health workers provide the bulk of emergency obstetric and neonatal care. In this context these cadres are defined as those who undertake roles and tasks that are more usually the province of internationally recognised cadres, such as doctors and nurses. While there have been several studies addressing retention factors for doctors and registered nurses, data and studies addressing the perceptions of these mid-level cadres on the factors that influence their performance and retention within health care systems are scarce. Methods This exploratory qualitative study took place in four rural mission hospitals in Malawi. The study population was mid-level providers of emergency obstetric and neonatal care. Focus group discussions took place with nursing and medical cadres. Semi-structured interviews with key human resources, training and administrative personnel were used to provide context and background. Data were analysed using a framework analysis. Results Participants confirmed the difficulties of their working conditions and the clear commitment they have to serving the rural Malawian population. Although insufficient financial remuneration had a negative impact on retention and performance, the main factors identified were limited opportunities for career development and further education (particularly for clinical officers) and inadequate or non-existent human resources management systems. The lack of performance-related rewards and recognition were perceived to be particularly demotivating. Conclusion Mid-level cadres are being used to stem Africa's brain drain. It is in the interests of both the government and mission organizations to protect their investment in these workers. For optimal performance and quality of care they need to be supported and properly motivated. A structured system of continuing professional development and functioning human resources management would show commitment to these cadres and support them as professionals. Action needs to be taken to prevent staff members from leaving the health sector for less stressful, more financially rewarding alternatives.